Aesthetics of Sufi Symbolism in the Poetry Collection “There Is Nothing in the Cloak but the Sea” by Fatah Aalaq - mighirach, othmane (El Omda in Linguistics and Discourse Analysis, 2023)
The Sufi symbol is the most important manifestation of thematic diversity in Arabic poetry in particular. The poets found in it what they wanted, so they used it as an alternative to what is prevalent, and what is familiar. Sufis among them see clarity as an obstacle between him and what he wants to express and deliver to the recipient, so he resorted to the reference because it is the most informative From the phrase and through the subconscious is a metaphor for the apparent and the direct, for the symbol for them is the technical tool and the only way to reveal its hidden secrets, and to get out of the monotony of the direct familiar system and the world of matter to the worlds of the unseen, mystical and spiritual, penetrating the vernacular language into a special language that is more complex and ambiguous.